Influence of dietary pattern on anti-tuberculosis treatment outcomes in persons with dysglycemia: a Peruvian prospective cohort study - Arriaga, María B.; Araújo-Pereira, Mariana; Andrade, Vanessa M. B.; Queiroz, Artur T. L.; Fernandes, Catarina D.; Sales, Caio; Aliaga, Juan Gonzalo; Shivakoti, Rupak; Lecca, Leonid; Calderon, Roger I.; Andrade, Bruno B. (Frontiers in Nutrition, 2023)
Introduction Dietary patterns (DPs) are associated with overall nutritional status and may alter the clinical prognosis of tuberculosis. This interaction can be further intricated by dysglycemia (i.e., diabetes or prediabetes). Here, we identified DPs that are more common with tuberculosis–dysglycemia and depicted their association with tuberculosis treatment outcomes. Methods A prospective cohort study of persons with tuberculosis and their contacts was conducted in Peru. A food frequency questionnaire and a multidimensional systems biology-based analytical approach were employed to identify DPs associated with these clinical groups. Potential independent associations between clinical features and DPs were analyzed. Results Three major DPs were identified. TB–dysglycemia cases more often had a high intake of carbohydrates (DP1). Furthermore, DP1 was found to be associated with an increased risk of unfavorable TB outcomes independent of other factors, including dysglycemia. Conclusion Our findings suggest that the evaluation of nutritional status through DPs in comorbidities such as dysglycemia is a fundamental action to predict TB treatment outcomes. The mechanisms underlying the association between high intake of carbohydrates, dysglycemia, and unfavorable tuberculosis treatment outcomes warrant further investigation.